2011
DOI: 10.1002/ijc.26042
|View full text |Cite
|
Sign up to set email alerts
|

The burden of cervical cancer in China: Synthesis of the evidence

Abstract: The burden of cervical cancer in China has not been characterized in detail. We reviewed cervical cancer data from national mortality surveys and registries, and conducted a meta‐analysis to estimate the prevalence of high‐grade lesions (HSIL) and high‐risk human papillomavirus (HR‐HPV) infections in rural Shanxi Province. We found that a national survey in the 1970s estimated age‐standardized cervical cancer mortality rates as ∼15 and ∼83/100,000 women nationally and in Xiangyuan, Shanxi; but the latest surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
110
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 27 publications
1
110
1
Order By: Relevance
“…In 1970s, the mortality of cervical cancer patients was approximately 9.98/100000 in China, while a survey reported that during the period from 1990-1992 the mortality was reduced to 3.25/100000 (Cao 2002). Despite this reduction, data has shown that the incidence of cervical cancer increased 14% during the period from 2000-20005 (Yang et al, 2000Shi et al, 2012). There are about 493,100 new cases of cervical cancer annually worldwide, and 273,000 women die of cervical cancer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1970s, the mortality of cervical cancer patients was approximately 9.98/100000 in China, while a survey reported that during the period from 1990-1992 the mortality was reduced to 3.25/100000 (Cao 2002). Despite this reduction, data has shown that the incidence of cervical cancer increased 14% during the period from 2000-20005 (Yang et al, 2000Shi et al, 2012). There are about 493,100 new cases of cervical cancer annually worldwide, and 273,000 women die of cervical cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, China has the largest population with cervical cancer. (Yang et al, 2000;Parkin et al, 2005;Li and Kang, 2011;Shi et al, 2012). Thus, developing an applicable method and screening program in China is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer remains the second most common cancer and the second most common cause of cancer-related death in China [9]. The main preventive measure against cervical cancer is cytology screening of exfoliated cervical cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is the second most aggressive type of malignant tumor, and causes serious damage to women's health (22). Each year, there are ~150,000 newly diagnosed cases of cervical cancer in China, which accounts for almost 1/3 of the total cases worldwide (12).…”
Section: Discussionmentioning
confidence: 99%